Capacity and power allocation for spectrum-sharing communications in fading channels - Musavian, L.; Aissa, S. (IEEE transactions on wireless communications, 2009)
This paper investigates the fundamental capacity limits of opportunistic spectrum-sharing channels in fading environments. The concept of opportunistic spectrum access is motivated by the frontier technology of cognitive radio which offers a tremendous potential to improve the utilization of the radio spectrum by implementing efficient sharing of the licensed spectrum. In this spectrum-sharing technology, a secondary user may utilize the primary user's licensed band as long as its interference to the primary receiver remains below a tolerable level. Herein, we consider that the secondary user's transmission has to adhere to limitations on the ensuing received power at the primary's receiver, and investigate the capacity gains offered by this spectrum-sharing approach in a Rayleigh fading environment. Specifically, we derive the fading channel capacity of a secondary user subject to both average and peak received-power constraints at the primary's receiver. In particular, considering flat Rayleigh fading, we derive the capacity and optimum power allocation scheme for three different capacity notions, namely, ergodic, outage, and minimum-rate, and provide closed-form expressions for these capacity metrics. Numerical simulations are conducted to corroborate our theoretical results.